INVITED EDITORIAL The UK NPM Reforms - Veggeland, Noralv (European Scientific Journal, ESJ, 2017)
The United Kingdom was a "vanguard state" for experimentation with administrative reforms that came to be known as the New Public Management or NPM strategies aiming market orientation of the public sector. After three decades, what results has NPM produced in the UK? This is a review of a research report by Christopher Hood and Ruth Dixon, who tries to explain maladministration and judicial challenges to nUK government actions.